The - Croswell, Ken (Oxford University Press, 1996)
In the last forty years scientists have made stunning discoveries about the Milky Way Galaxy, home of the Earth, Sun, and countless other stars. In the first popular account of these discoveries, Ken Croswell describes current thinking on the Milky Way and reveals how knowledge of the Galaxy can give us insight into the origins of the universe as a whole. He introduces us to the astronomers who have contributed to our understanding of the Galaxy, and explains new research showing that there may be a black hole at the centre of the Milky Way, with a million times more mass than the Sun, and that the oldest stars preserve the elements created in the big bang, thereby serving as `fossils' of the universe's earliest days. This book is intended for students and scientists working in the field of Astronomy. Anyone interested in the origins of the universe